Sosialisasi Coretax Sebagai Upaya Peningkatan Kepatuhan Pajak Pelaku UMKM Di Kota Bekasi - Keri Boru Hotang; R Taufik Hidayat (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
This community service program aims to enhance the understanding and tax compliance of Micro, Small, and Medium Enterprises (MSMEs) as an effort to support local economic growth in Bekasi City. The program was implemented using a combination of lecture-based material, hands-on practice, and interactive discussions, focusing on the comprehension of Income Tax regulations, ownership of Tax Identification Numbers (NPWP), and obligations for filing Annual Tax Returns (SPT). The results showed that the 30 participants demonstrated very high enthusiasm and a significant improvement in tax literacy and fiscal awareness, as evidenced by the post-test evaluation. According to the post-test data, the average participant score increased from 65% in the pre-test to 85% after the program. Additionally, participants showed a better understanding of the importance of proper financial record-keeping as a foundation for fulfilling tax obligations and implementing sustainable business governance practices. Overall, this program had a constructive impact on improving the awareness and tax compliance of MSME actors. The findings indicate that sustained collaboration among academics, local government, and tax authorities is essential. Follow-up programs, such as MSME tax clinics, regular mentoring, and the development of practice-based training modules, are recommended to systematically support the improvement of tax compliance in Bekasi City.